Solutions for a Class of Hadamard Fractional Boundary Value Problems with Sign-Changing Nonlinearity - Keyu Zhang; Zhengqing Fu (Journal of Function Spaces)
Using fixed point methods we establish some existence theorems of positive (nontrivial) solutions for a class of Hadamard fractional boundary value problems with sign-changing nonlinearity.